Anatomical Engineering and 3D Printing for Surgery and Medical Devices: International Review and Future Exponential Innovations. (24th March 2022) - Cornejo, José; Cornejo-Aguilar, Jorge A.; Vargas, Mariela; Helguero, Carlos G.; Milanezi de Andrade, Rafhael; Torres-Montoya, Sebastian; Asensio-Salazar, Javier; Rivero Calle, Alvaro; Martínez Santos, Jaime; Damon, Aaron; Quiñones-Hinojosa, Alfredo; Quintero-Consuegra, Miguel D.; et al.
Abstract : Three-dimensional printing (3DP) has recently gained importance in the medical industry, especially in surgical specialties. It uses different techniques and materials based on patients' needs, which allows bioprofessionals to design and develop unique pieces using medical imaging provided by computed tomography (CT) and magnetic resonance imaging (MRI). Therefore, the Department of Biology and Medicine and the Department of Physics and Engineering, at the Bioastronautics and Space Mechatronics Research Group, have managed and supervised an international cooperation study, in order to present a general review of the innovative surgical applications, focused on anatomical systems, such as the nervous and craniofacial system, cardiovascular system, digestive system, genitourinary system, and musculoskeletal system. Finally, the integration with augmented, mixed, virtual reality is analyzed to show the advantages of personalized treatments, taking into account the improvements for preoperative, intraoperative planning, and medical training. Also, this article explores the creation of devices and tools for space surgery to get better outcomes under changing gravity conditions.